Strengthening the accountability mechanisms as a strategy to counter the risk of corruption in the public sector of the Maldives / Fathimath Rasheed ... [et al.] - Rasheed, Fathimath; Said, Jamaliah; Ismail Khan, Norziaton (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
Corruption is a complex and prevalent worldwide problem that affects nearly every country on the planet. The Maldives is no exception to the corruption problem, having experienced a loss of over 5.4 billion US dollars from government funds over the past decade. Accountability is championed as a mechanism to curb corruption. As such, this paper attempts to investigate the relationship between accountability and corruption risk within the Maldives public sector. Using organization as a unit of analysis, data was collected using an online questionnaire survey from the procurement and human resources departments of each government ministry and the Councils of the Maldives. A total of 434 questionnaires were emailed from which 205 responses were received and usable. The data was analyzed using PLS-SEM, showing a significant negative relationship between accountability and corruption risk. Interviews with subject-matter experts served to further validate the findings. The study emphasizes that addressing corruption necessitates a cultural shift toward accountability, offering valuable insights for policy decisions in the Maldives and other nations tackling corruption challenges.